Sosialisasi Keamanan Pangan Jajan Anak Sekolah sebagai Upaya Peningkatan Taraf Kesehatan Masyarakat - Ika Nurfajri Mentari; Jumari Ustiawaty; Roushandy Asri Fardani; Desyani Ariza; Mohd Nazil Bin Salleh; Syahrul (Politeknik Medica Farma Husada Mataram, 2023)
Public health is a very important aspect to be considered in improving the welfare and progress of a country. Some of the health problems in childhood are stunting and nutritional imbalance. Conditions like this can have serious short-term impacts such as the risk of morbidity and mortality in infants and toddlers, medium-term impacts related to low intelligence and cognitive abilities, as well as long-term impacts related to the quality of human resources who experience degenerative disease disorders in the future. come. One of the efforts to avoid this is that the Health College Institution participates in providing knowledge to the community, especially elementary school children regarding school children's snacks. This activity was attended by 98 grade 5 and 6 students of SDN 1 Perampuan. The results obtained from these activities are that students understand and can distinguish between nutritious snacks and good for growth needs. In addition, students understand what will happen if they choose bad food with the ultimate goal of helping to improve people's lives, especially from the health aspect.